Dependence of Ga1-xMnxN Thin Films Growth on Substrate Temperature in Vertical MOCVD Reactor by Numerical Simulation - Budi Mulyanti; Fitri S. Arsyad; P. Arifin; M. Budiman; Sri Jatno W; M. Barmawi (Institut Teknologi Bandung, 2004)
Growth of Ga1-xMnxN thin film in the vertical MOCVD (Metal Organic Chemical Vapor Depositions) reactor as a function of substrate temperature is analyzed by numerical simulation. Gases that are used as a source of Ga, N and Mn are trimethylgallium (TMGa), nitrogen (N2) and cyclopentadienyl manganese tricarbonyl (CpMnTc), respectively. Hydrogen (H2) is used as a carrier gas for both TMGa and CpMnTc. The objective of simulation is to obtain an optimal growth parameter, in which the growth rate is high and uniform. From the simulation results, it can be concluded that to achieve a highest growth rate, the substrate temperature should be maintained at about 1173 K and with this temperature the growth rate is nearly constant when the susceptor radial distance is between 3.5 cm and 4.5 cm.